Telemedicine Application Adoption During the COVID-19 Pandemic: The Lens of the UTAUT Framework Model - Rahman, Beno; Prawitasari, Agata Pratiwi; Setiawan, Yulius Anggi; wijaya, Lianna (PT. BERBAGI TEKNOLOGI SEMESTA, 2024)
The objective of this study is to analyze the impact of various factors such as performance expectancy, effort expectancy, social influence, facilitating conditions, technology characteristics, task characteristics, and self-efficacy within the framework of the UTAUT model on the intention to adopt telemedicine applications, particularly in light of the ongoing Covid-19 pandemic. A quantitative approach is employed for data analysis, with data being gathered through the distribution of online questionnaires. The research sample consists of 350 respondents, and the data is examined using the Structural Equation Modeling (SEM) technique facilitated by the SmartPLS software. The findings reveal a positive and significant relationship between task technology fit and technology fit, as well as between technology characteristics and technology fit. Furthermore, task technology fit is shown to positively and significantly influence the intention to adopt telemedicine applications, where the services are anticipated to offer health assistance to users of the application. This study offers valuable insights for application developers to enhance features and services to attract public interest in utilizing telemedicine applications..